Strategi Pemasaran Digital Dalam Meningkatkan Daya Tarik Ekowisata Bahari Dan Minat Berkunjung Di Smiling Coral Indonesia - Fifiana Fifiana; Mochamad Chandra Wirawan Arief (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
Tourism plays a vital role in Indonesia's economic development, particularly through the advancement of marine ecotourism. Smiling Coral Indonesia (SCI) is a community-based organization focused on sustainable marine tourism and environmental conservation on Pramuka Island, Thousand Islands. This study aims to analyze the effectiveness of SCI's digital marketing strategies in enhancing tourist appeal and visit intention. Using a qualitative descriptive approach, data were collected through interviews, focus group discussions, direct observation, and content analysis of SCI’s Instagram account. The results show that SCI effectively utilizes visual content, interactive features, and strategic collaborations with influencers to increase digital engagement. Collaborative content and tourist experiences were found to generate the highest engagement levels, while conservation content strengthened brand consistency. Instagram serves as a primary source of information for potential visitors and influences their travel decisions. Furthermore, digital marketing has a positive impact on the local economy by increasing visitor numbers, promoting local products, and improving community welfare. The study concludes that integrating social media strategies with conservation values can significantly enhance the appeal and sustainability of marine ecotourism destinations.